A comprehensive view to deciphering of beneficial microbes’ status - A review - Kalaichelvi, K; Murali, S P; Ehab , A A S; Jeya , R M; Vinothini , S; Anantha , R P (Plant Science Today, 2025)
Even with advancements in technology, rapid population growth, soil degradation, loss of soil nutrients and a scarcity of food supply coupled with high demand are intensifying global crises like mortality, malnutrition, the rise of new diseases and widespread hunger. Consequently, global scientific efforts are increasingly focusing on using microorganisms in agriculture and related fields, often referred to as "green" or "organic agriculture." This approach encompasses a wide range of microbial applications, including biocontrol agents, biofertilizers, biopesticides and fermenters. It also leverages synthetic additives (e.g., Saccharomyces, Penicillium, Aspergillus), microbes for bioenergy and biogas production (Proteobacteria, Actinomycetes, methanogenic Archaea) and for enhancing nutrient content in foods (e.g., rice, maize, wheat). Furthermore, microorganisms are crucial for developing vaccines and medicines (Clonorchis sinensis Streptomyces spp., Saccharomyces cerevisiae, Penicillium chrysogenum) and facilitating bioremediation processes (Agaricus bisporus, Ganoderma lucidum, Phlebia radiata). These beneficial microbes are utilized based on their unique biometabolic pathways, offering a natural and eco-friendly solution that helps maintain food safety and ecological balance.